Association between tumor necrosis factor-α-308G/A gene polymorphism and susceptibility to pre-eclampsia: An updated meta-analysis. (November 2018) - Wang, Lingling; Qu, Guangbo; Wu, Wei; Tang, Xue; Sun, Yehuan
Highlights: There is a significant association of the tumor necrosis factor-α (TNF-α) 308G/A polymorphism and susceptibility to pre-eclampsia (PE) under allele model. Carriers of TNF-α (308A) allele would increase the susceptibility to PE, especially among Caucasian, Iranian and primipara. Abstract: Aims: Although two meta-analysis have reported no association between the tumor necrosis factor-α (TNF-α)-308G/A polymorphism and susceptibility to pre-eclampsia (PE), recent studies showed the association was still controversial. Thus, we conduct an updated meta-analysis to elucidate this association. Methods: Studies related to TNF-α-308G/A and PE risk were retrieved from PubMed, the Web of Science, Embase, Cochrane Library, CNKI, Wanfang, CBM, VIP Database. The odds ratios (OR) and 95% confidence intervals (CIs) were calculated to estimate the association between the TNF-α-308G/A polymorphism and susceptibility to PE under the models of allelic contrast (A vs. G), recessive (AA vs. AG+GG), dominant (AA+AG vs. GG), and co-dominant (AA vs. GG). Results: 22 studies (including 2459 cases and 4246 controls) were included in the meta-analysis. The overall analysis indicated that the significant association between TNF-α-308G/A polymorphism and susceptibility to pre-eclampsia existed in allele model (A vs. G: OR = 1.37, 95%CI: 1.06–1.77), but not in dominant model, recessive model, and co-dominant model. In subgroup analysis by ethnicity, pre-pregnancy BMI and pregnancy parity, the results showed the significant association between TNF-α-308G/A polymorphism and the risk of PE was obvious in Caucasian (A vs. G: OR = 1.36, 95%CI: 1.13–1.64; AA vs. GG: OR = 1.71, 95%CI: 1.03–2.86; AA+AG vs. GG: OR = 1.32, 95%CI: 1.03–1.71), Iranian (A vs. G: OR = 4.28, 95%CI: 2.01–9.11), and primipara (A vs. G: OR = 1.49, 95%CI: 1.15–1.92; AA vs. GG: OR = 2.15, 95%CI: 1.10–4.21). Conclusion: Current evidence demonstrates that carriers of TNF-α (308A) allele would increase the susceptibility to PE, especially among Caucasian, Iranian and primipara.